IMPACT OF STORAGE DAYS ON THE EMERGENCE OF TRICHOGRAMMA JAPONICUM ASHMEAD (HYMENOPTERA : TRICHOGRAMMATIDAE) - UMA, S.; BOHRIA, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Trichogramma japonicum Ashmead is commonly used biocontrol agent through inundative field release. The impact of storage of T. japonicum for different days (10, 15, 20, 25 and 30 days after parasitization) for different life stages (egg, larval and pupal) at 10°C was studied under laboratory condition. It was observed that there was significant reduction in adult emergence from parasitized Corcyra cephalonica (Stainton) eggs containing egg, larval and pupal stages of T. japonicum due to storage. Maximum adult emergence (59.4%) was observed when the egg stage of T. japonicum was stored for 10 days and percent adult emergence decreased upto 34.7% when storage period extended to 30 days. The percentage of adult emergence ranged from 55.8% (at 10 days after storage) to 33.7% (at 30 days of storage) in larval stage. Storage of T. japonicum at pupal stage (7 days after parasitization) exhibited maximum adult emergence (64.5%) as compared to both egg and larval stages.